Immune‐mediated thrombotic thrombocytopenic purpura prognosis is affected by blood pressure. Issue 4 (18th May 2022) - Joseph, Adrien; Eloit, Martin; Azoulay, Elie; Kaplanski, Gilles; Provot, François; Presne, Claire; Wynckel, Alain; Grangé, Steven; Rondeau, Éric; Pène, Frédéric; Delmas, Yahsou; Lautrette, Alexandre; et al.
Abstract: Background: The prevalence, prognostic role, and diagnostic value of blood pressure in immune‐mediated thrombotic thrombocytopenic purpura (iTTP) and other thrombotic microangiopathies (TMAs) remain unclear. Methods: Using a national cohort of iTTP ( n  = 368), Shigatoxin‐induced hemolytic uremic syndrome ( n  = 86), atypical hemolytic uremic syndrome ( n  = 84), and hypertension‐related thrombotic microangiopathy ( n  = 25), we sought to compare the cohort's blood pressure profile to assess its impact on prognosis and diagnostic performances. Results: Patients with iTTP had lower blood pressure than patients with other TMAs, systolic (130 [interquartile range (IQR) 118–143] vs 161 [IQR 142–180] mmHg) and diastolic (76 [IQR 69–83] vs 92 [IQR 79–105] mmHg, both p  < 0.001). The best threshold for iTTP diagnosis corresponded to a systolic blood pressure <150 mmHg. iTTP patients presenting with hypertension had a significantly poorer survival (hazard ratio 1.80, 95% confidence interval 1.07–3.04), and this effect remained significant after multivariable adjustment (hazard ratio = 1.14, 95% confidence interval 1.00–1.30). Addition of a blood pressure criterion modestly improved the French clinical score to predict a severe A disintegrin and metalloprotease with thrombospondin type 1 deficiency in patients with an intermediate score (i.e., either platelet count <30 × 10 9 /L or serum creatinine <200 µM). Conclusions: Elevated blood pressure at admission affects the prognosis of iTTP patients and may help discriminate them from other TMA patients. Particular attention should be paid to blood pressure and its management in these patients.